Sustainable Management of Challenges in the Agri-Food Supply Chain: the Case of Upcountry Vegetable Farmers in Nuwara Eliya District, Sri Lanka - Rathnachandra, S.D. Dilini; Malkanthi, S.H. Pushpa (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2025)
This study aimed to identify the challenges associated with the sustainable management of the agri-food supply chain, with a particular focus on the upcountry vegetable sector. Additionally, it sought to develop strategies to address these challenges and establish mechanisms to further enhance sustainable supply chain management. A sample of 300 vegetable farmers from the Nuwara Eliya district was selected using a simple random sampling method. Data collection was undertaken between July and October 2024 through a field survey and two focus group discussions. Descriptive statistics and Garrett’s Ranking technique were applied to analyse the quantitative data obtained from the survey. The qualitative data from the focus group discussions were analysed using thematic analysis. The findings revealed several key social challenges to sustainable development in agri-food supply chains, including limited access to agricultural inputs, insufficient awareness about managing these supply chains and low adoption of modern technologies. Major economic challenges identified included high production costs, inadequate financial support, difficulties for small-scale farmers in competing in both domestic and international markets, and poor knowledge of using ICT for market information. As the environmental challenges included long-distance transportation of products, limited product diversification capabilities and threats to entering export markets through maintaining the product quality. Hence, the study suggests providing concessional financial support for purchasing agricultural inputs, conducting awareness programmes to improve knowledge and experience in managing supply chains, introducing modern technologies to encourage the adoption of best practices, implementing strategies to reduce production costs, developing market information systems with better ICT access and improving transportation and opportunities for producing diversified agri-food products.